The three Abrahamic faiths and their roles in making peace, unity and co-existence - Ali, Md. Yousuf (IDOSI, 2011)
The three Divine Abrahamic faiths i.e. Judaism, Christianity and Islam, revealed to the prophets of God, are divine religions that shape outlook of life, people’s perception, culture and civilization and enhance the relationship between God-man-universe. In this process, people who adhere to a particular religion tend to explore the phenomena through the lens of religion. However, throughout the history of religions, it has been observed that three faiths provoked people to live with peace, love, unity and co-existence but ideological divergence, religious extremism and political interest led people to involve with aggression, violence and destruction such as Crusades of Christian Europe against Muslims and Islam-phobia. In contemporary world, after the post-9/11, the world community observes hatred, violence, conflict, aggression and religious extremism between the Muslims and non-Muslims that contributed distrust, disunity and unsteadiness because of prejudice and unequivocal ignorance against each other. In these turmoil situations, the followers of the three faiths through dialogue can play a vital role for establishing world security, justice, peace and unity in shaping a better prosperous future for the entire humanity. Therefore, this study examines critically the roles of the three Abrahamic faiths i.e. Christianity, Judaism and Islam for making peace, unity and coexistence through the transformation of moral, religious and socio-cultural values for shaping a better prosperous future for the entire humanity. In particular, the study focuses on: a) understanding ethical and moral obligation and cultural integrity through moral values transformation, b) realizing three common religious faiths, values and communal responsibilities towards God, fellow human beings and other creatures, c) understanding sociocultural aspects of each other through dialogue and d) identifying causes for divergence and discrepancy among the followers of three Abrahamic faiths. This study also intends to elaborate briefly the necessity of building bridges in society. The following two key issues will be critically examined. The first concerns the question of the transformation of ethical, religious and socio-cultural values through dialogue. The second concerns the question of the causes of divergence among the followers of three Abrahamic faiths with some recommendations and suggestions in bridging the gap and reducing the tension between the Western and the Muslim World. Discussion would include implications of the research findings, shortcomings of the current study and directions for future research.